Evaluating the impact of peer supplemental instruction on STEM course outcomes: A five-semester study at an HBCU - Brown, Lisa D.; Winborne, Duvon G. (American Journal of STEM Education, 2025)
This study examined the impact of Supplemental Instruction (SI) on student performance in introductory STEM courses at a Historically Black College or University (HBCU). Using a non-experimental, ex post facto design, academic outcomes from 105 courses and 2,829 student grades were analyzed over five semesters. While overall course performance scores did not significantly differ between SI and non-SI groups, SI-supported courses showed significantly higher frequencies of “B” and “C” grades and a greater proportion of passing rates. These findings suggest that SI may improve academic outcomes for students at risk of failure. Institutions seeking to reduce attrition in gateway STEM courses—especially among underrepresented students—should consider SI as a scalable, equity-driven academic support model.